Model Kepemimpinan Transformasional Dalam Pengembangan Bakat Santri di Pondok Pesantren Salafiyah Al-Mu'awanah Kabupaten Bandung: Studi Kasus di Pondok Pesantren Salafiyah Al-Mu'awanah Jalan Cibiru Hilir Kabupaten Bandung - Munadilhaq, Ahmad; Junaedi, Jujun; Rachmawaty, Indira Sabet (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to examine the integrity and commitment, motivation and inspiration, intellectual stimulation, and individual consideration carried out by the leaders of pesantren in the development of students' talents. This research uses a descriptive method with a qualitative approach. Data was collected through observation, interviews, and document analysis. The study is based on Bass' (Insan, 2017) transformational leadership theory. The findings show that the pesantren leaders play an important role in providing motivation, inspiration, and individual attention to students to help them develop their talents. The leaders also provide space for creative innovation through intellectual stimulation and the development of practical skills. This research provides insights into the application of transformational leadership that can be implemented in the development of talents within the pesantren context.